Henry Adams. - Auchincloss, Louis (University of Minnesota pamphlets on American writers ;, 1971)
Henry Adams - American Writers 93 was first published in 1971. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.